Genomic and personalized medicine - Willard, Huntington F.; Ginsburg, Geoffrey S. (Elsevier/Academic Press, 2009)
This two-volume set provides an in-depth look at one of the most promising avenues for advances in the diagnosis, prevention and treatment of human disease. The inclusion of the latest information on diagnostic testing, population screening, predicting disease susceptibility, pharmacogenomics and more presents this book as an essential tool for both students and specialists across many biological and medical disciplines, including human genetics and genomics, oncology, neuroscience, cardiology, infectious disease, molecular medicine, and biomedical science, as well as health policy disciplines focusing on ethical, legal, regulatory and economic aspects of genomics and medicine.